A participação política de mulheres autodeclaradas pretas nas eleições de 2020 nas capitais do Centro-Oeste brasileiro - Silva, Sara Cristina Martins da (2023)
This research aimed to reflect, in the light of debates on gender and race, on the underrepresentation of black women in politics in the Brazilian Midwest. The questions that guided this investigation were: what difficulties do black women face when running for public office? How do gender oppressions relate to racial oppressions to prevent the rise of black women in politics? And why have the mechanisms created so far to encourage women in elections not yet been able to produce a real change in the number of women elected, especially self-declared black women? Thus, the general objective was to analyze the political participation of selfdeclared black women in the 2020 municipal elections in the three capitals of the Midwest region of Brazil. To achieve this general objective, (i) we mapped the candidacies of selfdeclared black women in the municipal elections of Cuiabá, Campo Grande and Goiânia and; (ii) we sought to understand the intersections of gender and race in the life trajectories of selfdeclared black women candidates in the municipal elections of Cuiabá, Campo Grande and Goiânia. This research was bibliographical in nature, drawing on references such as studies by Lélia Gonzalez, Grada Kilomba and bell hooks, among other black authors. We also used documentary research to analyze the data provided by the Superior Electoral Court (TSE), in order to map the female candidates taking part in the research, and field research, with the application of a questionnaire with open and closed questions, which obtained 23 responses from self-declared black female candidates, who ran in the municipal elections for the position of councillor in the municipalities of Cuiabá, Campo Grande and Goiânia. As a result of the research, we found that the problem goes far beyond legislation (but also goes beyond it), since in reality it reflects deep historical problems that are intricate with Brazilian social formation, which requires a political effort to overcome the oppressions that affect black women, which the gender quotas in force in Brazilian electoral legislation are insufficient to overcome. In addition, the responses collected show that the participants have a clear perception of the occurrence of racism and misogyny in their electoral trajectories, perpetrated by the electorate and political parties.